2016
DOI: 10.1016/j.ajog.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Persistent opioid use following cesarean delivery: patterns and predictors among opioid-naïve women

Abstract: Background The incidence of opioid-related death in women has increased five-fold over the past decade. For many women, their initial opioid exposure will occur in the setting of routine medical care. Approximately 1 in 3 deliveries in the U.S. is by Cesarean and opioids are commonly prescribed for post-surgical pain management. Objective The objective of this study was to determine the risk that opioid naïve women prescribed opioids after Cesarean delivery will subsequently become consistent prescription op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
220
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(231 citation statements)
references
References 27 publications
10
220
1
Order By: Relevance
“…44,47,5154 Even opioids prescribed for low-pain, outpatient, or short-stay surgeries increase the risk of persistent opioid use, 51,52 and over 60% of people receiving 90 days of continuous opioid therapy remain on opioids years later. 55 Patients receiving an opioid prescription after short-stay surgeries have a 44% increased risk of long-term opioid use.…”
Section: Persistent or Chronic Opioid Use After Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…44,47,5154 Even opioids prescribed for low-pain, outpatient, or short-stay surgeries increase the risk of persistent opioid use, 51,52 and over 60% of people receiving 90 days of continuous opioid therapy remain on opioids years later. 55 Patients receiving an opioid prescription after short-stay surgeries have a 44% increased risk of long-term opioid use.…”
Section: Persistent or Chronic Opioid Use After Surgerymentioning
confidence: 99%
“…56,59 Use of specific medications including preoperative benzodiazepines and antidepressants are also associated with persistent opioid use after surgery. 54,56,59 …”
Section: Predictors Of Chronic Opioid Use After Surgerymentioning
confidence: 99%
“…Recent population based studies that have investigated opioid utilization after surgery, have similarly found relatively short duration of opioid requirements after cesarean delivery. 11,12 In the study by Sun and colleagues, 12 chronic opioid use was defined as having filled 10 or more prescriptions or having obtained more than 120 days’ supply of opioids within 1-year after cesarean delivery. The absolute risk of opioid naïve women becoming a chronic opioid user was 0.12%, which was 28% higher risk than a matched non-surgical control population.…”
Section: Discussionmentioning
confidence: 99%
“…Bateman et al stratified opioid naïve women into 5 categories according to the pattern of medication filling after cesarean delivery to identify persistent opioid users. 11 They demonstrated that 0.36% of women fell into the category of persistent opioid users, who on average dispensed opioids in 6.1 out of 12 months following cesarean delivery. Our study is unique in providing daily opioid utilization data after cesarean delivery to outline use trajectories rather than just relative risk determinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation